2013
DOI: 10.1136/bcr-2013-009399
|View full text |Cite
|
Sign up to set email alerts
|

Fragment reattachment of fractured anterior teeth in a young patient with a 1.5-year follow-up

Abstract: SUMMARYCrown fracture of maxillary anterior teeth is relatively common among children and teenagers. Aesthetic rehabilitation of crown fractures of the maxillary anterior is one of the greatest challenges to the dentist. Reattachment of a fractured fragment to the remaining tooth can provide better and long-lasting aesthetics, improved function, a positive psychological response and is a faster and less-complicated procedure. This article presents a case of reattachment of anterior tooth with a coronal fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Also, another study reported a long term performance of this technique better than that of direct composite restoration (Cavalleri & Zerman 1995). If the fracture segment is about 50% of the crown a post treatment is recommended for better prognosis (Ninawe et al 2013). Many factors contribute to good prognosis of fracture reattachment procedure.…”
Section: Prognosismentioning
confidence: 99%
See 4 more Smart Citations
“…Also, another study reported a long term performance of this technique better than that of direct composite restoration (Cavalleri & Zerman 1995). If the fracture segment is about 50% of the crown a post treatment is recommended for better prognosis (Ninawe et al 2013). Many factors contribute to good prognosis of fracture reattachment procedure.…”
Section: Prognosismentioning
confidence: 99%
“…The treatment of the fracture teeth depends -a great extent -on the type of fracture if it is simple or complicated. Treatment of simple fracture was done either by direct composite restoration or a full coverage crown, while in the complicated cases root canal treatment with post and core and may be followed by full coverage porcelain crown was the treatment of choice (Ninawe et al 2013, Pavone et al 2015. The disadvantages of the first technique are the instability of the composite shade and long term discoloration while the second technique is too aggressive scarifying the tooth vitality and possible wear of the opposing dentition (Pavone et al 2015).…”
Section: Treatment Modalitiesmentioning
confidence: 99%
See 3 more Smart Citations